Property, Trusts and Succession - Gretton, George Lidderdale; Steven, Andrew J. M. (Haywards Heath, West Sussex Tottel Publishing Ltd., 2011)
Offers coverage of the property, trusts and succession part of the LLB syllabus in Scotland. This book covers the land law regime, as well as the subject of the Land Registration (Scotland) Act 1979 in the context of the planned reforms of the Scottish Law Commission. It is of interest to practitioners seeking an introduction to this area of law.
Include Appendix and Index.
Keywords: Trusts and trustees -- Scotland -- Inheritance and succession -- Real property -- Property